Reappraisal of Tashiroea as a genus independent of Bredia (Melastomataceae) based on molecular data - Kokubugata, Goro; Nakamura, Koh; Kuo, Wen-Hsi; Qi, Zhe-Chen; Chung, Kuo-Fang; Fu, Cheng-Xin; Suzuki, Yumiko; Yokota, Masatsugu (Phytotaxa, 2019)
Molecular phylogenetic analyses using ITS sequences were used to reconsider the taxonomic validity of Bredia okinawensis, B. yaeyamensis, and B. sinensis as an independent genus Tashiroea. The result showed that the three species formed a different phylogenetic lineage from other species of Bredia including its type species. We suggest that B. okinawensis, B. yaeyamensis, and B. sinensis should be treated as T. okinawensis, T. yaeyamensis, and T. sinensis, respectively, following Ito and Matsumura (1899) and Diels (1924).